2015
DOI: 10.5657/fas.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value and Bioactive Properties of Enzymatic Hydrolysates prepared from the Livers of Oncorhynchus keta and Oncorhynchus gorbuscha (Pacific Salmon)

Abstract: Calculated chemical scores (computed in relation to the FAO/WHO reference protein) for salmon liver protein hydrolysates indicated that all amino acids (other than methionine and threonine) were present in adequate or excess quantities; thus, the raw liver material is a good source of essential amino acids. The hydrophobic amino acids contents in hydrolysates prepared from Oncorhynchus keta and O. gorbuscha were 38.4 and 39.1%, respectively. The proportion of released peptides exceeding 500 kDa was reduced whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Rainbow trout roe protein hydrolysates were obtained via pepsin or Alcalase hydrolysis presented essential amino acids in a very interesting proportion [710]. In another paper, hydrolysates from the livers of Oncorhynchus keta and Oncorhynchus gorbuscha were produced using different proteases and Alcalase was the most efficient one [711]. The adequate amounts of essential amino acids, the balanced amino acid composition and the presence of some possible bio-active peptides, make the Alcalase liver protein hydrolysate a good alternative in functional food applications and as a source of novel products [711].…”
Section: Comparison Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…Rainbow trout roe protein hydrolysates were obtained via pepsin or Alcalase hydrolysis presented essential amino acids in a very interesting proportion [710]. In another paper, hydrolysates from the livers of Oncorhynchus keta and Oncorhynchus gorbuscha were produced using different proteases and Alcalase was the most efficient one [711]. The adequate amounts of essential amino acids, the balanced amino acid composition and the presence of some possible bio-active peptides, make the Alcalase liver protein hydrolysate a good alternative in functional food applications and as a source of novel products [711].…”
Section: Comparison Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…Huang et al analyzed proteins and potential bioactive peptides and revealed that tilapia skin collagen is a promising source for producing antithrombotic peptides . Yoon et al found that hydrolysates from Oncorhynchus keta showed higher antithrombotic efficacy compared to Oncorhynchus gorbuscha, with the Neutrase enzyme being more suitable for producing antithrombotic peptides than papain …”
Section: Application and Potential Role Of Bioactive Proteins And Pep...mentioning
confidence: 99%
“…28 Yoon et al found that hydrolysates from Oncorhynchus keta showed higher antithrombotic efficacy compared to Oncorhynchus gorbuscha, with the Neutrase enzyme being more suitable for producing antithrombotic peptides than papain. 29 Recent research focused on marine shellfish as a source for developing anticoagulant peptides. Anticoagulant peptides have been successfully isolated and purified from various marine shellfish proteins, including oyster, mussel, scallop, clam, and more.…”
Section: Application and Potential Role Of Bioactive Proteins And Pep...mentioning
confidence: 99%
“…Combined with their tetraploid origin, life history diversity, and rate of diversification, they have generated significant interest from the research community. Equally important, salmon is considered an excellent source of nutrients such as amino acids, lipids, vitamins, and minerals [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The problem remains that many salmon populations are declining, and great efforts are directed toward their conservation, especially in relation to anthropogenic factors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%